2022
DOI: 10.1111/jcal.12755
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthy remote assessments: A typology of pedagogical and technological strategies

Abstract: Background: Online learning has grown significantly during the past two decades, and COVID-19 pandemic has expedited this process. However, previous research has shown how academic dishonesty is more prevalent under these modalities.Therefore, there is the challenge of performing trustworthy remote assessments, in order to obtain valid and reliable measures of students' knowledge.Objectives: The research question that drove this research was: what actions have been proposed in contemporary research to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…In another study, 86% of learners reported concerns about network connectivity (Snekalatha et al, 2021). Hilliger et al (2022) published a thematic review of papers published in a special issue of the Journal of Computer Assisted Learning. They identify eight recommendations from the published articles including determining the type of remote assessment appropriate for the task, paying attention to the design of assessment tasks, communicating with learners, and creating shared understandings about what constitutes academic dishonesty.…”
Section: Academic Integrity and Remote Proctoringmentioning
confidence: 99%
“…In another study, 86% of learners reported concerns about network connectivity (Snekalatha et al, 2021). Hilliger et al (2022) published a thematic review of papers published in a special issue of the Journal of Computer Assisted Learning. They identify eight recommendations from the published articles including determining the type of remote assessment appropriate for the task, paying attention to the design of assessment tasks, communicating with learners, and creating shared understandings about what constitutes academic dishonesty.…”
Section: Academic Integrity and Remote Proctoringmentioning
confidence: 99%
“…De hecho, no son problemas exclusivos de la evaluación en línea, sino comunes en la evaluación universitaria y en otras etapas educativas (Surahman & Wang, 2022). Reconducir y resolver estas problemáticas pasa, por una parte, por un cambio de actitudes y por conductas honestas, lícitas y éticas y, por otra, en la utilización de la propia tecnología para detectar, disminuir y desincentivar estas prácticas fraudulentas (Hilliger et al, 2022).…”
Section: Un Breve Contexto Históricounclassified
“…Studies have highlighted the common challenges faced in online assessments, including cheating and plagiarism, issues faced by teachers in making and conducting online assessments, concerns raised by students, and technical and financial issues faced by institutions [42]. The integrity of online university assessments has been examined, revealing concerns such as students cheating and resource unavailability, hesitancy to adopt online assessment systems, and fear of losing examination integrity [43] Remote Learning Security Ensuring the security of remote learning environments, including video conferencing and collaboration tools, is crucial to prevent unauthorized access and protect students' online safety [44]. The paper discusses the adoption of emergency remote learning during the COVID-19 pandemic and the security risks associated with it.…”
Section: Digital Learning Platformsmentioning
confidence: 99%